APPLICATION OF QGARCH MODELS TO NIGERIA INSURANCE STOCKS - SUNDAY, ARUNA, U.; ADENOMON, M.O. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
This study used QGARCH model to analyze insurance stock in Nigeria. The data used in the study are daily insurance stocks obtained from Nigeria Stock Exchange for a period of 1961 – 2019. The analysis done in this study were conducted in R-environment using Rugarch package by Ghalanos and E-view. Four competing QGARCH models such as QGARCH (1,1), QGARCH (1,2), QGARCH (2,1) and QGARCH (2,2) with student t’s distribution were considered. However, the model made used of necessary parameters, half-life and persistence to undertake the study. Model selection was based on Akaike information – criterion (AIC). Although all the models were fit because their respective values of persistence do not exceed one. In terms of performance for the distributions QGARCH (1,1) supersedes the rest models with all the parameters significant. It becomes pertinent that in modeling financial time series of insurance stocks QGARCH Models should be adopted to be able to obtain an optimum result.